(untitled) (Scientific Journal of the Dragomanov Ukrainian State University Series 2 Computer-Oriented Learning Systems, 2020)
Based on the analysis of scientific and methodical sources and requirements for the recipients of contemporary information education, the paper establishes the relevance of the implementation of a practice-driven approach to the learning of the fundamentals of data protection and the need to develop the set of relevant practical tasks. According to the aim, the paper depicts the set of didactic tasks of various types for the implementation of the said approach in the field of information education. Tasks of all types are designed to form the students’ experience of implementation the earned knowledge to the solution of real-life problems on data protection issues. Solving of the developed set of tasks will help youth to acquire sustainable skills of using contemporary data protection tools, to form their socially conscious attitude to real threats to information security and correct behavior in case of dangerous situations. According to the current curricula for national educational institutions, training in computer science courses related to these issues is aimed at forming in students a system of relevant knowledge and skills, and the acquisition of certain skills. Accordingly, to characterize the developed system of tasks for the implementation of a practice-oriented approach to learning the basics of data protection. The relevance of the introduction of a practice-oriented approach to learning the basics of data protection is established and the need to develop a set of relevant practical tasks is determined. The implementation of such a system of tasks for the implementation of a practice-oriented approach will help young people gain sustainable skills in the use of modern data protection tools. Learning the basics of information security and data protection occupies a leading position in information education at both secondary and higher levels.